2010
DOI: 10.1074/jbc.m110.133991
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of UNC-51-like Kinase 3 (Ulk3) in the Sonic Hedgehog Signaling Pathway

Abstract: The Sonic hedgehog (Shh) signaling pathway controls a variety of developmental processes and is implicated in tissue homeostasis maintenance and neurogenesis in adults. Recently, we identified Ulk3 as an active kinase able to positively regulate Gli proteins, mediators of the Shh signaling in mammals. Here, we provide several lines of evidence that Ulk3 participates in the transduction of the Shh signal also independently of its kinase activity. We demonstrate that Ulk3 through its kinase domain interacts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 59 publications
(35 reference statements)
2
58
0
Order By: Relevance
“…As it has been shown previously, inhibition of Ulk3 expression using plasmids expressing Ulk3 -specific shRNA led to stronger increase of Gli1 mRNA expression in response to Shh than it was achieved in the control cells after 48 h of treatment [6]. The same phenomenon was observed in the present study in two experimental models and may be explained by up-regulation of Ulk3 and Gli2 to the levels higher than in the control cells at late stages of RNAi experiments.…”
Section: Discussionsupporting
confidence: 91%
“…As it has been shown previously, inhibition of Ulk3 expression using plasmids expressing Ulk3 -specific shRNA led to stronger increase of Gli1 mRNA expression in response to Shh than it was achieved in the control cells after 48 h of treatment [6]. The same phenomenon was observed in the present study in two experimental models and may be explained by up-regulation of Ulk3 and Gli2 to the levels higher than in the control cells at late stages of RNAi experiments.…”
Section: Discussionsupporting
confidence: 91%
“…These findings, and the observation that Drosophila Su(fu) can partially substitute for murine SUFU in mouse embryo fibroblasts (Chen et al, 2009), suggest that SUFU silencing of Gli proteins in mice is also likely to be sensitive to analogous changes in phosphorylation produced by at least one Hh-stimulated protein kinase. Even though the murine protein kinase most similar in sequence to Drosophila Fu is not required for Hh signaling at least three other protein kinases (MAP3K10, Cdc2l1 and ULK3) have been found to contribute positively to Hh responses in cultured mammalian cells (Evangelista et al, 2008; Maloverjan et al, 2010; Varjosalo et al, 2008; Wilson and Chuang, 2010). It will be of great interest to see if these or other protein kinases are activated by Hedgehog ligands, perhaps promoted by association with Smo-Kif7 complexes in a positive feedback loop, and whether they can antagonize mSUFU to activate Gli proteins, and perhaps even stabilize Gli proteins via Kif7 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are known to be involved in different biological processes. For example, Ulk1 and Ulk2 are major regulators of autophagy (Ro et al, 2013); Ulk2 is reported to be involved in the development of some brain areas such as the habenula (Taylor et al, 2011); Ulk3 is involved in the regulation of the Sonic hedgehog signaling pathway (Maloverjan et al, 2010) that plays a crucial role in brain development (Fuccillo et al, 2006); moreover, deficiency of Stk36 or Ulk4 leads to a hydrocephalus-like phenotype (Merchant et al, 2005;Vogel et al, 2012). These data suggest that Ulk4 family members could be critical for the development and function of the nervous system.…”
Section: Introductionmentioning
confidence: 99%